Reversible cerebral vasoconstriction syndrome and posterior reversible encephalopathy syndrome in a boy with Loeys‐Dietz syndrome. (22nd June 2015) - Akazawa, Yohei; Inaba, Yuji; Hachiya, Akira; Motoki, Noriko; Matsuzaki, Satoshi; Minatoya, Kenji; Morisaki, Takayuki; Morisaki, Hiroko; Kosaki, Kenjiro; Kosho, Tomoki; Koike, Kenichi
Abstract : Loeys‐Dietz syndrome (LDS) is an autosomal dominant connective tissue disorder, caused by heterozygous mutations in TGFBR1 or TGFBR2 and characterized by vascular complications (cerebral, thoracic, and abdominal arterial aneurysms and/or dissections) and skeletal manifestations. We here report the first patient with LDS presenting with reversible cerebral vasoconstriction syndrome (RCVS), a clinico‐radiological condition characterized by recurrent thunderclap headaches, with or without neurological symptoms, and reversible vasoconstriction of cerebral arteries. The patient was a 9‐year‐old boy with a heterozygous TGFBR2 mutation, manifesting camptodactyly, talipes equinovarus, and lamboid craniosynostosis. He complained of severe recurrent headaches 2 months after total aortic replacement for aortic root dilatation and a massive Stanford type B aortic dissection. A thoracic CT scan revealed a left subclavian artery dissection. Brain MRI and MRA detected bilateral internal carotid artery constriction along with a cortical subarachnoid hemorrhage without intracranial aneurysms. Subsequently, he developed visual disturbance and a generalized seizure associated with multiple legions of cortical and subcortical increased signals including the left posterior lobe, consistent with posterior reversible encephalopathy syndrome (PRES), a condition characterized by headaches, visual disorders, seizures, altered mentation, consciousness disturbances, focal neurological signs, and vasogenic edema predominantly in the white matter of the posterior lobe. Vasoconstriction of the internal carotid artery was undetectable 2 months later, and he was diagnosed as having RCVS. Endothelial dysfunction, associated with impaired TGF‐β signaling, might have been attributable to the development of RCVS and PRES. © 2015 Wiley Periodicals, Inc.